The use of soxhletation method and microwave-assisted extraction in extracting tannin from jengkol peel (Pithecellobium jiringa). Issue 1 (March 2021) - Tambun, R; Husna, R; Fitri, M D; Ginting, Y; Alexander, V
Abstract: This study aims to compare the ability of the Soxhletation method and Microwave-Assisted Extraction in extracting tannin from Jengkol peel. The solvent used in both extraction methods is ethanol. In the Soxhletation method, the operating conditions performed are heating at a temperature of 70 °C for 6 hours, while the operating conditions at Microwave-Assisted Extraction are using a microwave power of 100 W with extraction time of 180 seconds. The ratio of samples and solvents in both methods is 1: 6 and 1:10. Based on the results of the study, the highest tannin content obtained from Jengkol peel extract using ethanol solvent is by using Microwave-Assisted Extraction, which is equal to 11.94% in the ratio of sample and solvent is 1:10. In the Soxhletation method, the highest tannin content obtained in the Jengkol peel extract is 10.72%, which is achieved in a sample and solvent ratio of 1:10.